Clinical practice guideline on traditional Chinese medicine therapy alone or combined with antibiotics for sepsis - Zhao, Guo-Zhen (Ann Transl Med, 2019)
BACKGROUND: To develop the clinical practice guidelines for the treatment of sepsis with traditional Chinese medicine (TCM) therapy alone or TCM combined with antibiotics. METHODS: The methods and process for developing the international clinical practice guidelines were fully consulted between a group of doctors. A total of 25 experts from 14 units were involved in the development of this guideline. The major clinical questions that needed to be solved were raised first, and the best available evidence to solve them was researched. Finally, according to the principle set by the GRADE system, the available evidence was graded with levels ranging from high to low. This formed the recommendation strengths, which included strong recommendation and weak recommendation, or an expert consensus recommendation. RESULTS: The guideline identified the terms and definition for sepsis. For example, it identified its epidemiological characters, the advantages of TCM treatment on sepsis, the diagnosis and its features, the complications, and its rehabilitation and health maintenance. The guideline has put forward 14 recommendations, among which 4 were strong recommendations and 6 were weak recommendations, in addition to 4 expert consensus recommendations. CONCLUSIONS: The methods and processes for developing international clinical practice guidelines were fully consulted under the guide of relevant laws and regulations, and relevant technical documents. Based on the best existing evidence, and combined with the characteristics of TCM and the clinical realities, we developed Clinical practice guidelines for the treatment of sepsis with TCM therapy alone or TCM combined with antibiotics, with full reference to the experts’ experience and patients’ preferences.